PERAN SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK DALAM MENDUKUNG KEPEMIMPINAN EFEKTIF PADA OPERASI SAR - Kusworo Kusworo; Ika Sartika (Jurnal Caraka Prabu, 2025)
This study aims to analyze the role of Electronic-Based Government Systems (SPBE) in supporting effective leadership in the implementation of Search and Rescue (SAR) operations, particularly in the context of disaster management. Using a literature review approach, this study examines various scholarly findings and policy documents related to the implementation of SPBE in emergency response processes, focusing on speed, accuracy, and inter-agency coordination. The findings indicate that SPBE plays a strategic role in accelerating decision-making through the provision of real-time data, technology-based geographic mapping systems, and digital communication between institutions. However, its implementation faces several challenges, including limited digital infrastructure in disaster-prone areas, low digital literacy among human resources, and the suboptimal integration of information systems across national and regional agencies. This study recommends strengthening digital leadership, integrating disaster information systems into a unified platform, and enhancing human resource capacity and ICT infrastructure as strategic steps to optimize the role of SPBE in supporting adaptive and responsive SAR leadership in disaster dynamics.